The physical and Chemical Impact of Microplastic in The Marine Environment: a Systematic Review - Anis Tatik Maryani; Yudha Gusti Wibowo; Kerlin Maysatria (Sriwijaya Journal of Environment, 2020)
Marine environment reported has been decreasing in water quality caused by microplastic. This micro-particle generated from contamination of ultraviolet light with plastic debris on the environment. Microplastic has been found in several marine environments and made some problems especially for marine ecosystem, such as beach, river and sea. This article described microplastic source, technique for detection and analysis of microplastic in marine environment, physicochemical of microplastic including physical properties such as particle size, particle shape, crystallinity, etc and chemical properties of microplastic (i.e. toxicity and chemical compounds). This article discusses the impact of microplastic for environment and human health. Thus, this article has described the systematic information about microplastic in the marine environment.